Capital Market and Financial Development on Growth: A Panel ARDL Analysis - Appiah, Michael; Frowne, Derrick Yaw Idan; Tetteh, Derrick (UI Scholars Hub, 2020)
This study evaluates the influence of capital market development and financial development ongrowth in the three West African countries. Data used for the research is from the World Bank and Pen World Table (PWT). This research uses the Panel ARDL test to examine the long-term relationship, as well as the error correction model to analyze the existence of a short-term relationship. The results show that in both the long term and short term, there is a negative influence of capital market development on economic growth. On the same line, in the long term, financial development is also negatively associated with growth and has no significant impact on economic growth. The ECM results indicate that there is a long-run causality effect between capital market development, financial development, and economic growth.